A discussion on different approaches for prescribing physical interventions - four roads lead to Rome, but which one should we choose? - Herold, F.; Törpel, A.; Hamacher, D.; Budde, H.; Gronwald, T. (Journal of Personalized Medicine, 2020)
It is well recognized that regular physical exercise has positive effects on physical and mental health. To use the beneficial health effects of physical exercise, there are worldwide movements encouraging health care providers to include physical exercise in their care and treatments strategies. However, a crucial point in administering the "exercise polypill" is the dosing and, in turn, the prescription of the physical intervention (PI). In this perspective article, we discuss the advantages and disadvantages of different approaches to prescribe PI. In this context, we also highlight outstanding questions and potential areas of opportunity for further investigations.